2022
DOI: 10.5194/tc-2022-27
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental Conditions for Snow Cornice Formation tested in a Wind Tunnel

Abstract: Abstract. Snow cornices growing on the lee of mountain ridges are a common feature in alpine and polar regions during snow seasons. They can result in potential avalanche risk when they crack and fall. Current studies of cornices mainly focus on their deformation, collapsing, and avalanche risk via field observations. Few studies have paid attention to the accretion process of cornices, especially on their horizontal growth which enhances the instability of cornices. In this work, experiments in a cold laborat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…During snow transport events, the wind flow erodes the snowpack in the most exposed regions and leads to snow re-deposition in sheltered areas. Therefore, the formation of bedforms, like dunes and ripples (Filhol and Sturm, 2015), as well as cornices at the leeward side of mountain crests (Hancock et al, 2020;Yu et al, 2022), are often observed. Snow sublimation is enhanced because the snow particles aloft are more exposed to the dry air flow (Liston and Sturm, 2004;Déry et al, 1998;Dai and Huang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…During snow transport events, the wind flow erodes the snowpack in the most exposed regions and leads to snow re-deposition in sheltered areas. Therefore, the formation of bedforms, like dunes and ripples (Filhol and Sturm, 2015), as well as cornices at the leeward side of mountain crests (Hancock et al, 2020;Yu et al, 2022), are often observed. Snow sublimation is enhanced because the snow particles aloft are more exposed to the dry air flow (Liston and Sturm, 2004;Déry et al, 1998;Dai and Huang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The wind is well documented as a major snow transport process (e.g., Schmidt, 1980;Li and Pomeroy, 1997;Li et al, 2018). It creates cornices (e.g., McCarty et al, 1986;Kobayashi et al, 1988;Yu et al, 2022) and mountaineers agree on the importance of wind in the formation of SBs. It is indeed unlikely that the creep affecting the top snow layers (Teufelsbauer, 2011) 5 is sufficient for a snow cornice (i.e.…”
Section: Introductionmentioning
confidence: 99%